(untitled) (Nigerian Journal of Pharmaceutical Research, 2026)
Background: Intracellular gum extracted from the stem bark of Cissus populnea has potential applications in pharmaceutical, cosmetic, and food industries. However, in its native form, the gum is associated with starch from the storage sites in the stem. Alpha amylase hydrolysis of the associated starch may improve the physicochemical properties and functions of the resultant gum. Objective: The objective of this study is to investigate the effect of purification of the native gum extracted from the stem bark of Cissus populnea by hydrolysis of the associated starch using alpha amylase. Methods: Cissus populnea gum (CPG) was extracted by cold aqueous maceration and precipitated with 98% ethanol and dried in a hot air oven at 60°C for 1 h to obtain the native CPG. The polymer was further purified by introducing α-amylase enzyme with constant stirring at 70°C for 4 h to obtain the starch-free CPG. Both native and starch-free CPG were evaluated to elucidate the physicochemical properties. Results: The extraction yield of the native and starch-free CPG was 33.5 and 29.3%, respectively. Enzyme hydrolysis significantly improved viscosity, moisture content, and moisture sorption capacity, which were 20.03, 5.63, and 19.14, respectively (compared to the native CPG). The purity and flow properties of the hydrolysed CPG were higher than those of the native. Conclusion: The enzyme-hydrolysed Cissus populnea gum (CPG) exhibited improved physicochemical and flow properties, making it suitable for industrial and pharmaceutical applications in solid (tablets) and semi-solid (suspensions and emulsions) formulations.